Services marketing - Palmer, Adrian (Henry Stewart Talks, 2012)
Service based economies, Effects of intangibility, inseparability and perishability, Designing service processes, Industrialisation of services, Service failure and recovery, The interface between services marketing, operations management and human resource management, Managing demand and capacity for services, Service quality, Service dominant